Meningkatkan Proses Pembelajaran Tematik Menggunakan Pendekatan Cooperative Learning Tipe Think Pair Share (TPS) di Kelas IV SD Negeri 42 Korong Gadang Kecamatan Kuranji Kota Padang - Oktaviani, Oktaviani; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study attempts to improve student learning process  in integrated thematic learning through used the of cooperative learning approach type think pair share (TPS) to the fourth grade students of SDN 42 Korong Gadang Kecamatan Kuranji Kota Padang. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with three meetings covering four stages, namely planning, implementation, observation, and reflection.. This study was conducted at SDN 42 Korong Gadang Kecamatan Kuranji Kota Padang to 20 students. The results of the study: (1) percentage The learning plan, namely 78,12% (enought) to 92,85% (Very Good). (2) The implementation of learning from  aspect of teacher, of 75% (enough) to 92.85% (Very Good). (3) The aspects of students of 80% (good) to 95% (Very Good). It can be concluded that the Discovery Learning model can improve the integrated thematic learning process in elementary schools.